Dejados Atras: El Regreso Glorioso: Los Ultimos Dias - Book 12 - LaHaye, Tim F.; Jenkins, Jerry B.; Rivers, Nellyda (Miami, FL : Editorial Unilit, 2004)
After seven years, the remaining members of the Tribulation Force are gathered at Petra, trying to find a way to stop Nicolae Carpathia, the Antichrist, and his forces, while awaiting the return of Christ.
Keywords: Fiction; Spanish language -- Reading materials